OCCURRENCE PATTERNS AND POPULATION DENSITY OF BARKING DEER (MUNTIACUS VAGINALIS) IN THE SOUTHERN SLOPES OF HIMALAYA FOOTHILLS, PUNJAB, PAKISTAN - Habiba; M. Anwar; R. Khatoon; B. M. Khan; K. A. Nasir (Journal of Animal and Plant Sciences, 2020)
Barking deer is a small-sized cervid mammal and in Pakistan its population are limited to outer Himalayan foothill forests of Punjab Pakistan. They are usually associated with low but dense thorn scrub of Acacia modesta, Olea ferruginea and Zizyphus nummularia. Occupancy modelling was used to assess how environmental factors influence occurrence probabilities. The population parameters of barking deer were examined in Murree, Kotli-Sattian and Kahuta National Parks through direct visual observations and indirect signs of animal from 2015-2017. To estimate population density, distance sampling of the line transect data was employed. Mean population density was 0.27 individuals / km². The range of encounter rates in each study site was 0.04 to 0.43 per km of transect. Population density in summer was higher (0.43/km²) than in winter (0.36/km²), possibly due to the addition of new-borns in May. The barking deer is basically a solitary animal. This species is endangered in Pakistan and its population are declining. Conservation efforts with focus on protection of disturbance-free habitat for barking deer are recommended in the study area.
Keywords: Barking deer; Murree; Kotli Sattian Kahuta National Park; Occupancy modelling; Occurrence patterns; Population density